Extreme Thermal Shielding Effects in Nanopaper Based on Multilayers of Aligned Clay Nanoplatelets in Cellulose Nanofiber Matrix. Issue 19 (6th October 2016) - Carosio, Federico; Kochumalayil, Jose; Fina, Alberto; Berglund, Lars A.
Abstract : Thin films consisting of highly aligned clay nanoplatelets embedded in cellulose nanofiber matrix can withstand the penetration of a flame torch (temperature ≈ 900 °C) with a stable temperature drop >600 °C on the unexposed side. Clay nanoplatelets provide high through‐thickness interface density and thermal shielding properties, while nanocellulose expands to form thermally stable carbonaceous residue connecting clay platelets.